Pengaruh Komunikasi dan K3 (Keselamatan dan Kesehatan Kerja) Terhadap Kinerja Karyawan PT Sinergi Aitikom Jakarta Selatan - Azah Mareli Palestina; Pusporini Palupi Jamaludin (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to investigate the extent to which communication and occupational health and safety (OHS) influence employee performance at PT Sinergi Aitikom, South Jakarta, both partially and simultaneously. The research problem is based on the importance of effective communication and the implementation of OHS in creating a safe, productive work environment, and supporting the achievement of optimal performance. The research approach uses a quantitative method with an associative design, which allows for analysis of relationships between variables. The independent variables include communication (X1) and occupational health and safety (OHS) (X2), while the dependent variable is employee performance (Y). The study population is all 81 employees of PT Sinergi Aitikom, and because the number is relatively small, a saturated sampling technique is used so that the entire population becomes the research sample. Data analysis was conducted through validity and reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination (R²), and hypothesis testing using t-tests and F-tests. The results showed that the OHS variable significantly influences employee performance, as indicated by a calculated t-value of 10.698, which is greater than the t-table (1.990), with a significance value of 0.000 (<0.05). Furthermore, the F-test results reinforced this finding, with a calculated F-value of 304.857, which is greater than the F-table (3.11), and a significance value of 0.000 (<0.05). This proves that communication and OHS simultaneously have a strong influence on employee performance. The coefficient of determination (R²) of 0.887 indicates that 88.7% of the variation in employee performance can be explained by communication and OHS, while the remaining 11.3% is influenced by other factors outside this study. Thus, effective communication and sound OHS implementation have proven to be key factors in improving employee performance in the company.